Dukunolide D from the Root of Lansium domesticum Corr. cv Kokosan - Suryana, Angela; Alimuddin, Andi Hairil; Rudiyansyah, Rudiyansyah (Chimica et Natura Acta, 2025)
Lansium domesticum has three varieties and one of the varieties is kokosan. These plants contain limonoids as the main constituents. Phytochemical investigation of L. domesticum cv kokosan has identified onoceranoids-type triterpenoids and tetranortriterpenoids from the seeds, fruit peels, and bark except for the root. This research described dukunolide D (1) that has been obtained from the methanol extract of the root of kokosan. Methanol root extract was fractioned by n-hexane and dichloromethane (DCM). All fractions including the crude extract were screened for phytochemical test. The DCM fraction was chromatographed in order to obtain compound 1. DART-HRMS of compound 1 showed a positive ion peak at m/z 469.1861 [M+H]+ (calculated 469.1862 corresponding for C26H29O8). The structure of 1 was fully determined by 1D (1H-NMR, 13C-NMR, and DEPT-135) and 2D NMR (COSY, HSQC, HMBC, and NOESY), and by comparison with data from literature.